Exosomes Released by Corneal Stromal Cells Show Molecular Alterations in Keratoconus Patients and Induce Different Cellular Behavior - Víctor Lozano; Carla Martín; Noelia Blanco; Ignacio Alcalde; Luis Fernandez-Vega Cueto; Jesús Merayo-Lloves; Luis M. Quirós (Biomedicines, 2022)
Exosomes have been related to various disorders, but their study in relation to ocular pathologies has been limited. In this article, we analyze exosomes produced by corneal stromal cells from healthy individuals and from patients with keratoconus. The proteomic study allowed for the identification of 14 new proteins with altered expression, related to molecules previously associated with the pathology. miRNA analysis detected 16 altered species, including miR-184, responsible for familial severe keratoconus. The prediction of its potential biological targets identified 1121 genes, including some related to this pathology. Exosomes produced by keratoconic cells induced a marked increase in the migration of stromal cells and corneal epithelium, while those produced by healthy cells had no effect on stromal cells. Both types of nanovesicles reduced the proliferation of stromal and corneal cells, but those produced by healthy cells had less effect. Exosomes produced by healthy cells had concentration-dependent effects on the transcription of genes encoding proteoglycans by keratoconus cells, with a relative normalization observed at concentrations of 240 µg/mL. These results show the alteration of stromal exosomes in keratoconus and suggest an influence on the development of the pathology, although the use of healthy exosomes could also have therapeutic potential.